Efficiency Study Of Quail Egg Marketing System At CV. Djion Puyuh In Somba Opu District Gowa Regency - Andy Hermawan; Imam Mustafa; Kharismafullah Kharismafullah; Manah (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study aimed to analyze marketing channels, marketing efficiency, farmers’ share, and the profit–cost ratio in quail egg marketing at CV Djion Puyuh, Somba Opu District, Gowa Regency. The study used qualitative and quantitative analyses. Data were collected through direct interviews with producers and marketing institutions involved in product distribution. Marketing channel analysis identified the flow of products and the institutions participating in each channel, while marketing function analysis examined exchange activities conducted by those institutions. Marketing margin was calculated as the difference between the price paid by consumers and the price received by producers. The results showed that CV Djion Puyuh used two marketing channels, both of which were categorized as efficient. This condition was reflected in a farmers’ share exceeding 50%, reaching 93%. The R/C ratio was greater than one, indicating that revenue exceeded marketing costs. Retailers earned a profit of IDR 2,000 with marketing costs of IDR 12,000, resulting in a profit–cost ratio of 16%. These findings indicate that the existing marketing system was economically efficient.